Carnaubeira fruit meal on performance and carcass yield of european quails (Research, Society and Development, 2020)
The objective of this work was to evaluate the addition of carbaubeira fruit meal (CFM) to replace corn, on the performance and carcass yield of European quails. Initially, the bromatological analysis of the CFM, was performed to determine the percentage of inclusion of it in the experimental diets. Six hundred, one day old, male and female European quails, were distributed in a completely randomized design composed of five treatments (increasing levels of corn substitution by CFM being 0, 4, 8, 12 and 16 % of inclusion), eight repetitions and 15 birds per repetition. Weekly, from 1 to 42 days of age, feed intake (FI), weight gain (WG) and feed conversion (FC) were evaluated. At 42 days after slaughter, slaughter weight, weight of noble cuts (breast and thighs) and organs (gizzard, cecum and small intestine) were determined. The data were subjected to analysis of variance and the means that showed a significant difference were compared using the Tukey and Dunnet tests (P